Hypofibrinogenemia is associated with a high degree of risk in infectious diseases: a post-hoc analysis of post-marketing surveillance of patients with disseminated intravascular coagulation treated with thrombomodulin alfa - Kazuo Kawasugi (Thrombosis Journal, 2021)
Abstract Background In patients with infectious diseases, disseminated intravascular coagulation (DIC) is often diagnosed without the fibrinogen value. The relationship between hypofibrinogenemia and outcomes of DIC in infectious diseases has thus remained unclear. Methods We analyzed 3204 patients who received with thrombomodulin alfa (TM-α) for DIC and suspected DIC. Hypofibrinogenemia was defined by a fibrinogen level < 1.5 g/L. Results Hypofibrinogenemia was observed in 10.3% of patients with infectious diseases. The frequencies of both bleeding and organ failure symptoms, and the scores for organ failure or the DIC diagnostic criteria were significantly higher in infectious disease patients with hypofibrinogenemia, suggesting that in patients with infectious diseases, hypofibrinogenemia is associated with more progressive and severe DIC. Although the 28-day survival rate and the DIC resolution rate were both significantly lower for infectious disease patients with DIC with hypofibrinogenemia than for those without hypofibrinogenemia, this difference was not observed in DIC patients with hematological diseases. Conclusions Hypofibrinogenemia among infectious disease patients with DIC may reflect increased consumption of fibrinogen due to accelerated coagulation reactions, while hypofibrinogenemia among hematological disease patients with DIC may be caused by fibrinogenolysis due to hyperfibrinolysis, and frequently results in bleeding and multiple-organ failure.